Direct Urca Processes with Hyperon-Hyperon Interactions - 喻孜 丁文波 (Communications in theoretical physics, 2011)
With a weak hyperon-hyperon （YY） interaction deduced from the new experimental data of AA potential, this paper has performed a calculation of the direct Urca （DURCA） processes in the framework of the relativistic mean field theory （RMFT） including σ＊ and φ mesons, in comparison with the results calculated with the strong YY interaction and with no （σ＊ ,φ ） mesons included. In neutron star matter, the weak YY interaction supplies the additional repulsive interaction between hyperons while the strong YY interaction supplies the attractive one. With the weak YY interaction, the effective masses of hyperons are larger than those with the strong YY interaction while smaller than those with no （σ＊ ,φ） mesons included. The threshold star masses for the DURCA processes involving nucleons and A are not sensitive to the strength of the YY interaction. The weak YY interaction leads to larger threshold masses for the DURCA process involving [1]1 and [1]0 than the other two cases. The process involving [1]0 can take place in the neutron star only when the weak YY interaction is used. The weak YY interaction is able to bring in the agreement with the observation of the neutron star with larger mass and faster cooling than the strong YY interaction.